The Role of Neutrophil to Lymphocyte Ratio (NLR) and Platelet to Lymphocyte Ratio (PLR) in Appendicitis - Heriyanto, Moch Junaidy; Ratnaningsih, Tri; Heriyanto Putri, Rona Hafida; Fatimah, Bunga; Astuti, Fardhiasih Dwi (JBN (Jurnal Bedah Nasional); Vol 8 No 1 (2024): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2024.v08.i01.p01, 2023)
Aim: Predictive values of neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are associated with poor outcomes in several diseases. Furthermore, there has been limited publication of those parameters in appendicitis patients in Indonesia. This study aims to evaluate the role of NLR and PLR in differentiating complicated appendicitis and uncomplicated appendicitis. Methods: The design of this study is a retrospective using medical records of appendicitis patients from January 1, 2016, to December 31, 2020, conducted at PKU Muhammadiyah Bantul Hospital. There are 408 data on appendicitis patients that can be analyzed. Results: The WBC, neutrophils, NLR, and PLR was significantly higher in the complicated appendicitis group than in the uncomplicated group [11,5 (3.79-35.2) vs. 8.42 (3.32-39.30), p < 0.0001; 8.63 (2.359-2.647) vs. 5.446 (1.691-35.960), p < 0.0001; 5.65 (0.95-23.86) vs.3.82 (0.81-23.86), p < 0.0001; 168.57 (37.27-974.03) vs.139.40 (56.84-1274.31), p < 0.0001, respectively] followed by a significantly lower lymphocyte count [1.709 (0.154-5.71) vs. 2.094 (0.401-5.812), p < 0.0001, respectively]. The area under the receiver operating characteristic (ROC) curve, cutoff point, sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and likelihood ratio of NLR for diagnosis of complicated appendicitis were 0.76, >2.84, 75.21%, 62.65%, 74.6%, 63.4%, 2.01, 0.40, respectively. In contrast, an area under ROC curve, cutoff point, sensitivity, specificity, PPV, NPV, and likelihood ratio of PLR for differentiating complicated and uncomplicated appendicitis were 0.605, >140.6, 65.70%, 51.81%, 66.5%, 50.9%, 1.36, and 0.66 respectively. Conclusion: The cutoff values of NLR (>2.84) and PLR (>140.6) were significant diagnostic parameters for complicated appendicitis (p = 0.0001). Hence, NLR and PLR can assist in diagnosing complicated appendicitis .